Managing Complexity, Reducing Perplexity Modeling Biological Systems - Delitala, Marcello.; Delitala, Marcello.; Ajmone Marsan, Giulia.; Ajmone Marsan, Giulia. (Springer Proceedings in Mathematics & Statistics, 2014)
This book is devoted to an overview of the status of the art in the study of complex systems, with particular focus on the analysis of systems pertaining to living matter. Both senior scientists and young researchers from diverse and prestigious institutions with a deliberately interdisciplinary cut were invited, in order to compare approaches and problems from different disciplines. The common aim of the contributions is to analyze the complexity of living systems by means of new mathematical paradigms that are more adherent to reality and which are able to generate both exploratory and predictive models that are capable of achieving a deeper insight into life science phenomena.